(3CUhd JQcjH GdCOhjIs - (3GdfLjH GdSeQbfOj , eMeO Hf Ydj Hf YeQ GdSeQbfOj, fLjH GdOjf CHh MGeO,J (B619 (3g` s ((3CMeO Hf eMeO GdMdHi s)
(3ChdgG (B:s
(3bGd GdTjN GdaGVd eMeO Hf Ydi GdSeQbfOi Ef GdhGLH Ydi cd Pi dH Cf jJbQH Edi Gddg hjJhSd Edjg hCMSf GdhSGFd hCLhO GdPQGjY EeJKGd GdChGeQ hGdfhGgi eGjYhO Ydi faY GdfGS YGeg s
(3BNQgG (B:s
(3jVQ GdeKGfI dCfgG hJbWY GdMGaI GdUaQGhjI dCLdi EHWGd GdZdjGf GdeMOK deGOJgG HMQGQJg hGddg CYde s
(3Vef eLehY s
(3GfXQgG eY OaY GdSehe Qbe (B" 467"s
(3fSNI KGdKI ef GdbSe GdKGdK ef GdfLjHjGJs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B280 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B31s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B270 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdWHs